The potential of biochar to remove hydrophobic compounds from model sandy soils - Peter Douglas (Geoderma, 2017)
Charcoals have long been used to adsorb organics from water and other substrates; we hypothesise that biochar may act in a similar way when mixed with soil, removing hydrophobic organic compounds from the soil surfaces. To test this hypothesis, we developed quantitative methods for addition of two hydrophobic organic compounds (octadecane and octadecanoic acid, commonly found in naturally hydrophobic soils) to, and their subsequent extraction from, acid washed sand (as a model for sandy soil). We then measured the quantity of the organic compounds which remained on the sand after: deposition; subsequent addition of 0, 1, 5, 10, 25 or 40 % wettable biochar; and storage for 1, 10, and 30 days in solutions of pH 3, 6 or 9. We found that there were small reductions in hydrophobic compound on sand with 1 and 5 % biochar additions, but that 10 % biochar removed ~ 50 %, and ≥ 25 % biochar removed ~ 100 %. The significance of these results in understanding the potential of wettable biochar to remove hydrophobic compounds from sandy soils, and thus act as an ameliorant of soil water repellency, is discussed.